2018
DOI: 10.14444/5051
|View full text |Cite
|
Sign up to set email alerts
|

Management of Metastatic Spinal Cord Compression in Ireland: Are Surgeons Overlooked?

Abstract: Background: The National Institute of Health and Clinical Excellence (NICE) provide a framework of evidencebased guidelines for the management of metastatic spinal cord compression (MSCC). We aimed to compare our center's provision of service to these best practice guidelines and discuss key shortcomings with their implications for the spinal surgeon. Methods: Patients with radiologic evidence of MSCC over a 30-month period were identified using the hospital electronic radiological database. A chart review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Regarding patient diagnosis, the current study revealed that the most common patient diagnosis was breast(60%)followed by prostatic (23.3%),(10%) had Multiple myeloma and 6.66 % had other types of cancer, which is supported by Nakata E and et al 2020 (80 ) (81) , who reported that (26.8%) of studied patients had prostatic and lung cancer and only (14.6%) had breast cancer. This study and its results also against with to what was reported byShah S and et al 2021 (82) who reported that lung (37.9%), breast (17.2%), and renal (10.3%).This difference as a result of increased the females sample in the study.…”
Section: Regardingsupporting
confidence: 75%
“…Regarding patient diagnosis, the current study revealed that the most common patient diagnosis was breast(60%)followed by prostatic (23.3%),(10%) had Multiple myeloma and 6.66 % had other types of cancer, which is supported by Nakata E and et al 2020 (80 ) (81) , who reported that (26.8%) of studied patients had prostatic and lung cancer and only (14.6%) had breast cancer. This study and its results also against with to what was reported byShah S and et al 2021 (82) who reported that lung (37.9%), breast (17.2%), and renal (10.3%).This difference as a result of increased the females sample in the study.…”
Section: Regardingsupporting
confidence: 75%
“…Since multidisciplinary collaboration is paramount for the successful treatment of MSCC, the fact that only 34% of hospitals had a Board for MSCC and only 37% had set up a multidisciplinary protocol for patients with MSCC is a grave cause for concern. These results are in line with those from other countries [12][13][14]19] and suggest that there is room for improvement in the management of SCC in routine practice.…”
Section: Discussionsupporting
confidence: 88%
“…However, whether these methods are actually used in routine clinical practice is largely unknown. In fact, audits have reported inconsistencies between recommendations of clinical guidelines issued by the National Institute for Health and Care Excellence (NICE) and actual routine practice in the United Kingdom and Ireland [12][13][14].…”
Section: Introductionmentioning
confidence: 99%